(untitled) (Bangladesh Journal of Botany, 2024)
The aim of this study was to investigate the effect of Glomus mosseae (G. mosseae) on Na+ intercept ability in root tissues of Kosteletzkya virginica (K. avirginica) grown under salt stress. Pot experiments in greenhouse were carried out in K. avirginica inoculated with Glomus mosseae under 1% NaCl stress. The Na+, K+ concentrations, distribution and growth parameters of K. avirginica were analyzed. Salinization reduced phosphorus (P) and chlorophyll contents, root and shoot dry weight. Salinity dramatically increased Na+ concentrations, but decreased K+ contents and K+ / Na+ ratio in shoot and root significantly (p < 0.05). Inoculated plants showed higher P concentrations, dry weight in both roots and shoots than non-inoculated ones. Compared with non-inoculated plants, G. mosseae inoculation accumulated Na+ mainly in the roots, and maintained higher K+ / Na+ ratio in the shoots. The X-ray microanalysis of root transverse section showed that roots endoderm of inoculated plants could strongly retain the transport of Na+ to stellar parenchyma vessels maintaining more Na+ in the roots whereas keep higher K+ / Na+ ratio in the shoots than that of non-inoculated seedlings. The elevated Na+ intercept ability in root tissues of mycorrhizal plants may help in improving the tolerance of K. avirginica to salt stress. Bangladesh J. Bot. 53(4): 1081-1087, 2024 (December)